Examination of Vehicles Carrying Fast-Breaking Cargo (Eurasian Research Bulletin, 2022)
The expert concludes on the general condition of the vehicle. In the event of a positive conclusion regarding the general condition of the body, it is recommended to evaluate the vehicle for a period of three years according to the category originally established by the plant that produced it, and the vehicle is sent for carrying out the determination of its isothermal characteristics